The Effect of Elderly Fitness on Cholesterol Levels - Annisa Nur Nazmi; Yahya Afisena; Anita Dwi Ariyani (Jurnal Keperawatan, 2022)
Hypercholesterolemia is a disease that often attacks the elderly due to plaques sticking to the walls of blood vessels, resulting in blockage of blood vessels (atherosclerosis). One of the non-pharmacological treatments to treat hypercholesterolemia is fitness exercise. This study aims to determine the effect of fitness exercise on changes in cholesterol levels in the elderly at the Apel Posyandu in the Work Area of ​​the Sobo Banyuwangi Public Health Center in 2019. This research method is quasi-experimental and uses a pre-experimental research design in the form of a "one-group pre-test-post-test" design. The population in the study were 15 respondents, with a total sample of 15 respondents. The sampling technique used was Total Sampling and tested with the Wilcoxon match pair test. The results of the research before it was carried out were high cholesterol levels > 240 mg/dl as many as 8 respondents. And after the intervention normal cholesterol levels <200 mg/dl were 12 respondents. The results of the calculation of the Wilcoxon test statistical test using SPSS showed the results = 0.000 < = 0.05, which means that there is a significant influence between fitness exercise on changes in cholesterol levels in the elderly at the Apple Posyandu in the Work Area of ​​the Sobo Banyuwangi Public Health Center in 2019. The results of research that have been conducted The results showed that fitness exercise can reduce cholesterol levels in hypercholesterolemic elderly, so it is hoped that health workers can socialize the use of fitness exercise as a non-pharmacological therapy for elderly people with hypercholesterolemia.